Figur Orang Tua dalam Pendidikan Karakter Anak Perspektif Pendidikan Islam - Migfar Rivadah; Unik Hanifah Salsabila; Muhammad Amirudin Rosyid; M. Fajrul; Fikri Haikal (Al-Musannif, 2020)
The study aims to analyze the role of parents in educating children with character education in accordance with Islamic education. The method used is descriptive quantitative method with relevant data collection techniques from several scientific articles, books, and news. The results of this study indicate that parental figures greatly influence character education in children. Parents have a significant role in character education in children, that parents as facilitators, motivators, and role models for children. The role of parents is prioritized in educating children’s character given that the era of globalization is so rapid that it can affect the character of the nation’s children. Parents are always expected to be figures capable of internalizing the values of national character and Islamic character in children according to the times. So that children have a foundation that is in accordance with conditions they are currently facing so that it makes children responsive to the character education given by their parents.